6
n*(9 - 2) = 2*7 = 7n
((7+9-6)/1)/1 is 10.
100 - 1-2-3-4-5-6-7-8-9-9-8 => 100-)1+2+3+4+5+6+7+8+9+9+8) 100 - (62) 38 The Answer!!!!
9 - 6 + 7 + (2 x 10) = 30
6
The expression "7 more than the product of 6 and 9" can be written as 6 * 9 + 7. First, you calculate the product of 6 and 9 (6 * 9 = 54), then add 7 to get the final result. Therefore, the expression simplifies to 54 + 7 = 61.
6-2/9= 5 7/9
7
11/6 − 7/9 = 7/18
n*(9 - 2) = 2*7 = 7n
((7+9-6)/1)/1 is 10.
100 - 1-2-3-4-5-6-7-8-9-9-8 => 100-)1+2+3+4+5+6+7+8+9+9+8) 100 - (62) 38 The Answer!!!!
It is 3 and 1 over 7.
9 - 6 + 7 + (2 x 10) = 30
7/18 minus 5/6 is -4/9
Zero